A Framework of Indicators for Sustainable Road and Highway Infrastructure Development in Developing Countries: The Ghana Context - Dokyi, George Okyere; Tookey, John; Rotimi, Funmilayo Ebun; Osei, Kwame Kwakwa (Penerbit Universiti Sains Malaysia, 2024)
There is an increase in global concern about sustainability issues across all industrial sectors. Adopting sustainable highway infrastructure development is thus a crucial step toward achieving sustainable transport. This, in turn, is a key component of several sustainable development goals (SDGs) and targets in the 2030 Agenda for Sustainable Development. Most developing countries face significant sustainability challenges in constructing roads and highway infrastructure because of a lack of a comprehensive framework for sustainable road infrastructure. This study aimed to develop a framework for sustainable road and highway development. The study utilises a questionnaire survey and data were obtained from highway professionals, including contractors, consultants, environmental agencies, road agencies, researchers and academics. Inferential statistics were developed via Statistical Package for the Social Sciences (SPSS) version 26 to identify the critical indicators considered by all highway professional groups. The findings revealed 31 critical indicators, of which reducing material costs, complying with environmental requirements, contract documents and project specifications, and disaster-resilient designs emerged as the top three critical indicators, highlighting the importance of economic efficiency, responsible project execution and infrastructure resilience. In addition to bridging the gap in the literature from developing countries, the developed conceptual framework offers a structured approach to guide future initiatives in highway infrastructure development, emphasising the integration of a range of criteria for a holistic and sustainable approach.
Keywords: 33 Built Environment and Design; 3302 Building; 11 Sustainable Cities and Communities; 9 Industry, Innovation and Infrastructure; 12 Responsible Consumption and Production; 17 Partnerships for the Goals; 1202 Building; 3302 Building